2019
DOI: 10.15698/mic2019.07.682
|View full text |Cite
|
Sign up to set email alerts
|

Laundry and textile hygiene in healthcare and beyond

Abstract: The elimination of microbial contaminations from textile is an important aspect of laundering apart from the removal of stains and dirt from used and worn textiles. Although the framework for institutional laundering is well regulated to ensure hygienic cleanliness via the use of e.g. high temperatures and bleaching agents, there are several open points, especially in domestic laundering. In both cases, energy efficiency of appliances is a main driver for innovation and has resulted in a general decrease in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 41 publications
1
74
0
1
Order By: Relevance
“…Gram-negative strains exhibited the greatest response to Dettol, Clorox and 3 M and the lowest response to Gentoo at the first minute of the first dilution. These results indicated that Dettol, Clorox Original and 3 M are the most effective antimicrobial agents among the detergents included against tested strains in this study, which supports the results of previous studies (Jain et al, 2016;Olasehinde et al, 2008;Sickbert-Bennett et al, 2005;Bockmühl et al, 2019;McDonnell and Russell, 1999). This study has highlighted two important factors for increasing detergent efficiency against pathogenic bacteria that should be considered appropriate concentration and exposure time.…”
Section: Discussionsupporting
confidence: 91%
“…Gram-negative strains exhibited the greatest response to Dettol, Clorox and 3 M and the lowest response to Gentoo at the first minute of the first dilution. These results indicated that Dettol, Clorox Original and 3 M are the most effective antimicrobial agents among the detergents included against tested strains in this study, which supports the results of previous studies (Jain et al, 2016;Olasehinde et al, 2008;Sickbert-Bennett et al, 2005;Bockmühl et al, 2019;McDonnell and Russell, 1999). This study has highlighted two important factors for increasing detergent efficiency against pathogenic bacteria that should be considered appropriate concentration and exposure time.…”
Section: Discussionsupporting
confidence: 91%
“…Washing of clothes and bed linen in hot water at 60°C and drying them in sunlight inside out may help prevent persistence of infection. [ 27 28 29 30 ] Since direct contact and fomites play a significant role in the spread of infection, patients should not share their soaps, clothes, towels and bed linen. [ 31 ] Furthermore, it is also important that the clothes of infected patients be stored and washed separately in order to prevent spread of infection.…”
Section: Resultsmentioning
confidence: 99%
“…The main objectives of healthcare laundering are to remove visible soiling and reduce the microbiological load, to minimise the transmission of infections and prevent malodour (Bockmühl, Schages & Rehberg, 2019). Healthcare linens are laundered industrially, employing high temperatures (≥60 • C) and/or detergents and disinfectants for cleaning and decontamination of the textiles (Bockmühl, Schages & Rehberg, 2019).…”
Section: Current Healthcare Laundry Policiesmentioning
confidence: 99%
“…The main objectives of healthcare laundering are to remove visible soiling and reduce the microbiological load, to minimise the transmission of infections and prevent malodour (Bockmühl, Schages & Rehberg, 2019). Healthcare linens are laundered industrially, employing high temperatures (≥60 • C) and/or detergents and disinfectants for cleaning and decontamination of the textiles (Bockmühl, Schages & Rehberg, 2019). Healthcare uniforms are generally washed industrially, however in some countries they are laundered domestically by the healthcare worker, for example in the UK (NHS, 2020), Republic of Ireland (Health Protection Surveillance Centre, 2020) and in some hospitals in the USA (Nordstrom, Reynolds & Gerba, 2012).…”
Section: Current Healthcare Laundry Policiesmentioning
confidence: 99%